Acute appendicitis in a child of 4 years of age: diagnostic and management challenge in general practice - Dangal, Binod; KC, Archana; Chaudhary, Vivek (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Acute appendicitis is a common surgical emergency in children but rare before age 6 years. Due to atypical presentation, diagnosis is difficult in young children and very often these children face increase rate of complications. Maintaining a high index of suspicion at early childhood is important. Even with prompt diagnosis, controversy exists between medical versus surgical management. We report a rare case of acute appendicitis in child of 4 years of age who underwent surgery by a working general practitioner at remote setting of Nepal.